The effect of using web-based book creator on culinary arts learning outcomes of culinary arts education students - Siti Sutanti; Dian Agustina Dalimunthe; Laurena Ginting; Erli Mutiara (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
Study This aiming For analyze influence Use of Book Creator media web based on results Study students in the eyes studying art culinary Culinary Arts Education Study Program . Place study Program Study of Culinary Arts Education, State University of Medan. Research time month July -September 2024 . Population study all over Culinary Arts Education students who take subject Art Culinary as many as 90 students . The sampling technique sample class that is in a way random sampling. So that it is obtained sample class A as many as 31 people as class experiment and class B as many as 28 people as class control . Data collection techniques use results Study pre test and post test . Data analysis techniques data description , requirements testing analysis namely the normality test and the homogeneity test and hypothesis testing using the t-test. Research results show that , level trend results Study students who use art teaching materials Culinary based on web book creator including category tend very Good as big as 58.06 percent . Learning outcomes students who use Art textbook Culinary including category tend Enough by 53.57 percent . The results of the t-test analysis show there is positive and significant influence on the use of art teaching materials Culinary based on web book creator to results Study student , with t value count > t table (10,795 > 2,002) at the level significant 5 percent . This means art teaching materials Culinary based on web book creator can influence results Study student Unimed . Conclusion research ; use Book Creator as a learning medium proven web based more effective in support learning practical on the eyes studying art culinary.